Teachers’ Atttitudes toward the Use of L1 in the EFL Classroom - Suhayati, Lisa (Journal of Language Learning and Research (JOLLAR), 2018)
This study aims to determine the attitudes and beliefs of teachers regarding the use of L1 in EFL (English as a foreign language) and to describe the functions for which L1 was employed by the teachers. The participants of this study were 15 EFL teachers teaching at several schools in three provinces: Banten, West Java, and Jakarta (Indonesia). To collect data, the writer conducted Likert-scale survey and semi-structured interview to two teachers. The results showed that even though there were few of them were in doubt whether the use of L1 might negatively affect students? English learning, their attitudes were positive toward the use of L1 in the English classroom. The results also indicated that the teachers employed L1 in the classrooms as a teaching tool and as part of classroom management to maximize the learning outcomes.